With the eyes of others : Hungarian Artists of the Sixties and Seventies. - Szanto, Andras; Kürti, Emese; Fehér, David; Winkler, Nora (New York : Elizabeth Dee, 2017)
Attalai, Gabor ; Bak, Imre ; Beke, Laszlo ; Erdely, Miklos ; Ficzek, Ferenc ; Galantai, György ; Gayor, Tibor ; Gulyas, Gyula ; Hajas, Tibor ; Halasz, Karoly ; Haraszty, Istvan ; Hencze, Tamas ; Jovanovics, György ; Keserü Ilona, Ilona ; Kismanyoky, Karoly ; Ladik, Katalin ; Lakner, Laszlo ; Maurer, Dora ; Megyik, Janos ; Mehes, Laszlo ; Nadler, Istvan ; Pauer, Gyula ; Workshop, Pecs ; Perneczky, Geza ; Pinczehelyi, Sandor ; Szentjoby, Tamas ; Szijarto, Kalman ; Szombathy, Balint ; Tot, Endre ; Veto, Janos
With the Eyes of Others Hungarian Artists of the Sixties and Seventies, Elizabeth Dee, New York, 2017
boek
Keywords: Hongarije